Use of Marketing Instruments in Development of towns and regions: Case Study Slovakia - Milan Bucek; Renata Paulickova (European Regional Science Association (ERSA), 2003)
It is possible to apply the marketing conception also by managing and developing towns. Marketing as a scientific discipline has started to apply in specific conditions of managing of the public sector in 1980s. The interest in this discipline in the conditions of the Slovak Republic - young and accession country which is being prepared for the entry to the European structures - has been caused particularly by two facts: transformation of proprietary relations and democratization of control processes. In the first part of the papers the presentation concentrate on the theoretical approaches to the possibility of using the marketing instruments in conditions of the towns, causes of the origin of the marketing of towns, its specific items and barriers, opinion development on the marketing of towns and the process of marketing of towns itself with its significant phases: phase of analysis of the environment, marketing strategy creation, its implementation and control. We also stress the role of the specific instruments of marketing mix possibly used right in the sphere of marketing of towns - people, physical evidence, processes and partnership which widen the traditional conception of the four elements of the marketing mix (4 P) - product, price, place and promotion used by the town as a support of its offer. The marketing of towns uses practically the same instruments as for example the company marketing. Use of marketing conception in the conditions of towns can contribute to the better analysis of the needs of the inhabitants or the visitors of the towns to find the way of how to satisfy them better. It also helps to find ways how to locate some products of the town on the market and how to supply with them the certain groups. Very important in this case is the segmentation of the towns themselves as well as the customers (market). The segmentation of the town closely relates to the creation of the market positioning of the town. The positioning of the town means the place, which the certain town has been taken in imaginations of its customers in comparison with another competing towns. It reflects the image of the town, which is a part of unique and difference of the certain town and its offer. Among the marketing mix of the town the specific place belongs to the product, which is much more different and specific than the product in the classic conception. The important part of the marketing of the town is a marketing plan and a marketing strategy. The marketing plan should be connected to the spatial plan of the town - it should contribute to it. The marketing strategy means to find the way of filling the aims stated in the plan. The specific item of the marketing strategy of the town is the numerous subjects, which are taken into account by formulating the strategy. In conditions of the Slovak municipality, application of marketing in comparison with the EU countries is insufficient. In the second part of the papers presentation present the topical state of applying marketing from the endogenous and exogenous points of view in 123 Slovak towns on the base of the results of their research, which will take part in February - April 2003 within the form of the case study. They also define the most frequent barriers in applying the marketing instruments and the creation of the marketing strategy within the practice of the Slovak towns.
Keywords: 330